Label-free proteomic profiling identifies ECM-related alterations across regeneration states in human peripheral axonal neuropathies - Marina Damato; Soulaimane Aboulouard; Velia La Pesa; Francesco Gentile; Giulia Lunghi; Michela Perrone; Beatrice Pranzo; Elena Chiricozzi; Nilo Riva; Isabelle Fournier; Alessandro Romano; Angelo Quattrini; et al. (Journal of Physiology and Biochemistry, 2026)
Understanding the multiple mechanisms underlying peripheral nerve regeneration in humans is crucial for developing effective therapies for peripheral axonal neuropathies. Although i n vitro and in vivo studies have provided significant insights, human studies exploring the composition of proteome remain limited. The ECM plays a crucial role in nerve regeneration, influencing cell adhesion, proliferation, migration, and finally differentiation. In this study, we used a high-sensitivity, label-free liquid chromatography-mass spectrometry (LC-MS) method to investigate the global proteomic profile of human sural nerves aiming to identify molecular dynamics that promote or hinder nerve regeneration in well-characterized cohorts of patients with acute axonal injury, regenerating axonal neuropathy, and non-regenerating axonal neuropathy. Overall, 149 proteins were identified, of which 68 showed significant modulation across the groups. Proteins over-represented in regenerating nerves highlighted the multifactorial nature of regeneration, including immune modulation, debris clearance, cytoskeletal reorganization, axonal extension, and lipid transport. Conversely, structural myelin and neuronal proteins were significantly downregulated in non-regenerating nerves. Among the differentially expressed proteins, functional enrichment analysis revealed a significant overrepresentation of ECM-related components, providing compelling evidence that the ECM is not merely a passive scaffold, but an active driver of peripheral nerve regeneration.